KADAR PROTEIN, TENSILE STRENGTH, DAN SIFAT ORGANOLEPTIK MIE BASAH DENGAN SUBSTITUSI TEPUNG MOCAF - Arsyi Wintaha Umri; Nurrahman -; Wikanastri H (Jurnal Pangan dan Gizi, 2017)
The main ingredient to make a noodle is wheat flour, it affects the wheat flour import number in indonesia, making it significantly increased. To overcome that issue, the wheat flour has to be substitued by local flour, the mocaf flour. The general objective of this research is to determine protein content, tensile strength, and the organoleptic characteristics of noodles with mocaf substitution. The research method is experiments  type using completely randomized design (CRD) monofaktorial with mocaf substitution variation factor of 0%, 10%, 20%, 30%, 40%, 50% and 60%. The protein content, tensile strength,  and organoleptic characteristic of products were analyzed. The statistical analysis result showed the mocaf substitution quantity had effect on protein content, tensile strength value and organoleptic characteristic in each treatment. The best result of this research is noodle with  20% mocaf substitution,3,766% protein content, 0,4875 N/mm2 tensile strength number, and 2,72 average value of organoleptic characteristic. The  conclusion results of the research conducted on the mocaf substitution noodle showed the are real difference for each test performed, the correlation test showed the result of the protein content is directly proportionate to the tensile strength  number. Keywords: noodles, mocaf, protein content, and tensile strength